Early geological exploration of Seymour Island, Antarctica - Zinsmeister, William J (Geology and Paleontology of Seymour Island, Antarctic Peninsula, 1988)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Seymourøya; Vestantarktis; ekspedisjoner; forskning; geologi; hvalfangere; oppdagelsesreiser

I Palmer-arkipelet - Holtedahl, Olaf (H. Sørlie : 1878 27. oktober 1928, 1928)
Account of few days visit to Port Lockroy area, Graham Land, on board Norwegian whale factory ship, 1928, during "Norvegia" expedition, 1927-28.
Keywords: Antarktis; Norvegia ekspedisjonen; Vestantarktis